A novel BSD domain-containing transcription factor controls vegetative growth, leaf senescence, and fruit quality in tomato. (26th August 2020) - Fan, Youhong; Niu, Xiangli; Huang, Li; Gross, Rachel; Lu, Han; Hawkins, Madigan; Yuan, Yulin; Miao, Min; Liu, Yongsheng; Xiao, Fangming
Abstract: BSD (mammalian B TF2-like transcription factors, s ynapse-associated proteins, and D OS2-like proteins) is a conserved domain that exists in a variety of organisms, but its function has not been well studied. Here, we identified a novel BSD domain-containing protein (SlBSD1) in tomato ( Solanum lycopersicum ). Biochemical and microscopy assays indicated that SlBSD1 is a functional transcription factor that is predominantly localized in the nucleus. Loss-of-function and overexpression analyses suggested that SlBSD1 is a novel regulator of vegetative growth and leaf senescence in tomato. SlBSD1 -knockdown (-KD) plants exhibited retarded vegetative growth and precocious leaf senescence, whereas SlBSD1 -overexpression (-OX) plants displayed the opposite phenotypes. The negative role of SlBSD1 in leaf senescence was also supported by RNA-seq analysis comparing leaf tissues from SlBSD1 -KD and wild-type plants. In addition, contents of soluble solids were altered in fruits in the SlBSD1 -KD and SlBSD1 -OX plants. Taken together, our data suggest that the novel transcription factor SlBSD1 plays important roles in controlling fruit quality and other physiological processes in tomato, including vegetative growth and leaf senescence. Abstract : SlBSD1, a novel tomato transcription factor containing a BSD domain, positively regulates vegetative growth and fruit quality but plays a negative role in leaf senescence.